Interactive Multimedia as a More Effective and Engaging Solution for Visual Programming Learning - Achmad Darojat; Armedo Futhi Munadzar (Edu Komputika Journal, 2025)
This study developed and evaluated an interactive multimedia learning product for the Visual Programming course at Sekolah Tinggi Teknologi STIKMA Internasional. Using the ADDIE development model Analysis, Design, Development, Implementation, and Evaluation the research aimed to improve learning effectiveness and student engagement through multimedia-based instruction. The product, designed as an executable (EXE) application, includes six chapters integrating text, animation, video, quizzes, and interactive navigation. Validation involved four experts in content, media, language, and user interface, as well as student trials in both small-group and field settings. Expert validation results averaged 89.26%, categorized as highly valid, while student trials showed an average of 84.8%. Field testing indicated that all students achieved the course passing standard, with scores ranging from 60 to 100. These findings demonstrate that the interactive multimedia effectively enhances students’ comprehension, motivation, and learning outcomes. The results are consistent with the Cognitive Theory of Multimedia Learning, which emphasizes the integration of visual and verbal channels to optimize cognitive processing. Practically, the product benefits students, lecturers, and institutions by promoting independent learning and supporting digital transformation in education. Overall, the developed multimedia is considered valid, effective, and feasible as an innovative instructional medium for Visual Programming.